Use of the behaviour change wheel to improve everyday person-centred conversations on physical activity across healthcare - Hamish Reid; Ralph Smith; Wilby Williamson; James Baldock; Jessica Caterson; Stefan Kluzek; Natasha Jones; Robert Copeland (BMC, 2022)
Abstract Background An implementation gap exists between the evidence supporting physical activity in the prevention and management of long-term medical conditions and clinical practice. Person-centred conversations, i.e. focussing on the values, preferences and aspirations of each individual, are required from healthcare professionals. However, many currently lack the capability, opportunity, and motivation to have these conversations. This study uses the Behaviour Change Wheel (BCW) to inform the development of practical and educational resources to help bridge this gap. Methods The BCW provides a theoretical approach to enable the systematic development of behaviour change interventions. Authors followed the described eight-step process, considered results from a scoping review, consulted clinical working groups, tested and developed ideas across clinical pathways, and agreed on solutions to each stage by consensus. Results The behavioural diagnosis identified healthcare professionals' initiation of person-centred conversations on physical activity at all appropriate opportunities in routine medical care as a suitable primary target for interventions. Six intervention functions and five policy categories met the APEASE criteria. We mapped 17 Behavioural Change Techniques onto BCW intervention functions to define intervention strategies. Conclusions This study uses the BCW to outline a coherent approach for intervention development to improve healthcare professionals' frequency and quality of conversations on physical activity across clinical practice. Time-sensitive and role-specific resources might help healthcare professionals understand the focus of their intervention. Educational resources aimed at healthcare professionals and patients could have mutual benefit, should fit into existing care pathways and support professional development. A trusted information source with single-point access via the internet is likely to improve accessibility. Future evaluation of resources built and coded using this framework is required to establish the effectiveness of this approach and help improve understanding of what works to change conversations around physical activity in clinical practice.